Effectiveness of Bilateral Superficial Cervical Plexus Block as Part of Postoperative Analgesia for Patients Undergoing Thyroidectomy in Empress Zewditu Memorial Hospital, Addis Ababa, Ethiopia - Zemedu Aweke; Wosenyeleh A. Sahile; Sileshi Abiy; Nugusu Ayalew; Adugna A. kassa (Anesthesiology Research and Practice)
Introduction. The pain after thyroid surgery is considered of moderate intensity and short duration. Most trials showed significant reduction in pain intensity and severity of pain in patients for whom bilateral superficial cervical plexus block (BSCPB) was done. Objective. To assess the postoperative analgesic effect of BSCPB for thyroid surgery. Methods. Sixty six euthyroid patients were recruited and assigned to two groups (33 patients each). Group 1 BSCPB and Group 2 standard analgesia. The unpaired Student’s t-test and Mann–Whitney test were used for comparison. Statistical significance was stated at p value < 0.05. Results. The median postoperative pain score (NRS) was 3 in the BSCPB group and 5 in the control group (p=0.002). There was also statistically significant difference at 6th, 12th, and 24th hour showing a lower median pain score in the BSCPB group compared to the control group. The median time was (360 minutes) in the treatment group and (180 minutes) in the control group (p=0.0006). The median tramadol consumption within 24 hours is 0 mg in the BSCPB group compared to 100 mg in the control group (p=0.001). Conclusion and Recommendation. BSCPB done for thyroidectomy under general anesthesia decreases the postoperative pain score, total analgesia consumption, and time to first analgesia request.